Postnatal Evaluation of Cervical Ribs in Control Rats. Issue 16 (29th July 2017) - Mukerji, Pushkor; Glatt, Christine; Gannon, Shawn; Lewis, Joseph M.
Abstract : Background: Cervical ribs in rat fetuses have been widely reported to occur in controls as well as in response to various maternal chemical exposures. However, few evaluations of cervical ribs have been reported in rats postnatally. The available literature has indicated that the postnatal incidences of cervical ribs in control rats are no higher than in perinatal fetuses. Methods: In a developmental toxicity study in rats conducted by the inhalation route, a control group of 44 time‐mated female rats was exposed to filtered air only from gestation day (GD) 6 to 20, and divided into two cohorts. For one cohort, fetuses were removed from dams by laparohysterectomy for skeletal evaluation on GD 21. The other cohort of dams was permitted to deliver, and adult offspring were euthanized on postnatal day 65 for a subsequent postnatal skeletal evaluation of cervical ribs. Results: The incidence of cervical ribs (mean percentage of affected fetuses or adults per litter) was observed to increase during postnatal development, from 1.0% on GD 21 to 12.7% on postnatal day 65. Further evaluation is ongoing to determine whether these observations were attributable to the inhalation exposure conditions used in this study. Conclusion: These results, while limited to the evaluation of one skeletal alteration in control rats, support the need for additional research into the area of postnatal development of skeletal abnormalities observed in developmental toxicity studies and the relevance of these skeletal observations to human risk assessment. Birth Defects Research 109:1301–1304, 2017. © 2017 Wiley Periodicals, Inc.